A bizarre case of accessory larynx in an infant with OEIS syndrome - Wong, Timothy Leong Wei; Baki M.M.; Ishak S.; See G.B. (Elsevier B.V., 2018)
We report a bizarre case of accessory larynx in an infant with OEIS syndrome (omphalocele, cloacal exstrophy, imperforated anus & spinal defects). This is the first reported case in literature of a duplicate accessory larynx which is a mirror image of the true larynx. A congenital duplication of the larynx is a rare anomaly and can present in various forms. In this case, the infant presented with recurrent lung infection and inability to wean off oxygen. Scope revealed severe laryngomalacia in addition to the accessory larynx. Hence, supraglottoplasty was done with aim to resolve the lung and airway problem.